Renal Involvement in Preeclampsia: Similarities to VEGF Ablation Therapy - Janina Müller-Deile; Mario Schiffer (Journal of Pregnancy)
Glomerular VEGF expression is critical for the maintenance and function of an intact filtration barrier. Alterations in glomerular VEGF bioavailability result in endothelial as well as in podocyte damage. Renal involvement in preeclampsia includes proteinuria, podocyturia, elevated blood pressure, edema, glomerular capillary endotheliosis, and thrombotic microangiopathy. At least the renal signs, symptoms, and other evidence can sufficiently be explained by reduced VEGF levels. The aim of this paper was to summarize our pathophysiological understanding of the renal involvement of preeclampsia and point out similarities to the renal side effects of VEGF-ablation therapy.